CONTENT-BASED INSTRUCTION (CBI) IN SERVING AN INTERNSHIP: PERSPECTIVES FROM THAI PRE-SERVICE TEACHERS MAJORING IN ENGLISH - Sasiporn Phongploenpis (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The research objectives were to investigate the changes in the perceptions in relation to English language teaching (ELT) and the ability to teach English after the implementation of CBI held by two pre-service teachers. Furthermore, it aims to investigate the perceived strengths and weaknesses of CBI as well as factors in implementing it during their teaching internship. The research was conducted on two pre-service teachers majoring in English having their teaching internship in the 2016 – 2017 school year, in public schools in Bangkok and Samutprakarn, Thailand. Both quantitative and qualitative data was obtained via two sets of an online questionnaire with five rating scales-questions and open-ended questions. Based on the responses to the questionnaires, the implementation of CBI made changes in their perceptions of ELT regarding lesson planning, learning activities, learning media, learning evaluation, and subject knowledge. The abilities to teach English were perceived as improved after the CBI implementation. The findings of the study also indicate that the successful implementation of CBI required a careful selection of content which should be of interested to the students and relevant to their prior knowledge. This could be attributed to enhancing pre-service teachers’ awareness of their prospective students’ needs and more effective teaching content and methods.